2021
DOI: 10.3390/genes12101610
|View full text |Cite
|
Sign up to set email alerts
|

Comparative RNA-Seq Analyses of Solenopsis japonica (Hymenoptera: Formicidae) Reveal Gene in Response to Cold Stress

Abstract: Solenopsis japonica, as a fire ant species, shows some predatory behavior towards earthworms and woodlice, and preys on the larvae of other ant species by tunneling into a neighboring colony’s brood chamber. This study focused on the molecular response process and gene expression profiles of S. japonica to low (9 °C)-temperature stress in comparison with normal temperature (25 °C) conditions. A total of 89,657 unigenes (the clustered non-redundant transcripts that are filtered from the longest assembled contig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 57 publications
4
6
0
Order By: Relevance
“…The GO enrichment analysis of DEGs indicated that some biological processes, including response to stress, abiotic stimulus, temperature, and cold, as well as ribosome biogenesis were enriched in both genotypes (Fig. 2); this is in agreement with prior reports [25][26][27] . In the molecular function category, catalytic, binding, transferase, hydrolase, transporter, transmembrane transporter, oxidoreductase, and ATPase activity, as well as structural constituent of ribosome were among the highly enriched GO indicators in both genotypes.…”
Section: Resultssupporting
confidence: 91%
“…The GO enrichment analysis of DEGs indicated that some biological processes, including response to stress, abiotic stimulus, temperature, and cold, as well as ribosome biogenesis were enriched in both genotypes (Fig. 2); this is in agreement with prior reports [25][26][27] . In the molecular function category, catalytic, binding, transferase, hydrolase, transporter, transmembrane transporter, oxidoreductase, and ATPase activity, as well as structural constituent of ribosome were among the highly enriched GO indicators in both genotypes.…”
Section: Resultssupporting
confidence: 91%
“…Glycerol titers in the hemolymph of Spodoptera exigua increased significantly in response to RCH and it was dependent on the exposure period at low temperatures (Park & Kim, 2013). Glycerol biosynthesis genes are upregulated in a close ant species, Solenopsis japonica , according to our recent transcriptome research (Vatanparast & Park, 2021). The metabolomics in the flesh fly Sarcophaga crassipalpis has verified glycerol accumulation during RCH, as well as accumulation of two amino acids (alanine and glutamine), an extra polyol (sorbitol), and a sugar (glucose) (Michaud & Denlinger, 2007).…”
Section: Discussionmentioning
confidence: 98%
“…Protein kinases can phosphorylate proteins by transferring phosphate groups to specific substrate proteins, usually ATP or GTP as donors and serine, 10.3389/fevo.2023.1099015 threonine, and tyrosine as receptors (Krupa et al, 2004;Faucher et al, 2008). The regulation of fatty acid synthase and serine protease is part of the diapause program (Robich and Denlinger, 2005;Vatanparast and Park, 2021). The heat stress caused metabolic disorders which cause diapause in honeybees.…”
Section: Discussionmentioning
confidence: 99%